Dual-emitting phosphor-glass composites by the melt-quenching method for high-quality laser lighting. Issue 23 (1st December 2022) - Ding, Wenting; Zhang, Zeliang; Hou, Xin; Mei, Yang; Long, Deng; Ying, Leiying; Lu, Miao; Zhang, Baoping
Abstract: The development of color converters with excellent low-cost comprehensive indicators is of great significance in promoting the rapid development of laser lighting technology. In this work, low-cost phosphor-glass composites (PGC) including green-emitting Lu3 Al5 O12 :Ce 3+ (LuAG) and red-emitting CaAlSiN3 :Eu 2+ (CASN) phosphors were successfully prepared by the melt quenching method. Moreover, the two phosphor layers were uniquely designed to be separated in a stable dual-layer structure supported by the matrix glass. This double layer structure can effectively reduce the reabsorption in traditional mixed multi-color phosphors. The main emission of the PGC-Green exhibited high internal and external quantum efficiencies of 95% and 68.8%, respectively. Meanwhile, the PGC-Red can still achieve the purpose of supplementing red emission, which is conducive to obtaining a higher color rendering index (CRI). Furthermore, the content of the LuAG phosphor and the thickness of the PGC layer were adjusted to reach a balance between efficiency and color. The optimized PGC has a luminous flux of 507 lm at a laser excitation power density of 2.66 W mm −2 with maximum luminous efficiency of 190 lm W −1 . A stable correlated color temperature of 5600 ± 300 K with a high CRI of 84 was achieved, similar to the sunlight-color profile. In addition, the luminescence of PGC is only reduced by less than 10% at 458 K, showing excellent thermal stability. We believe that this work provides a novel design of high-performance PGC color converters coupled with traditional glass manufacturing processes.